2006
DOI: 10.1093/jnci/djj101
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of Predictors of Vitamin D Status and Cancer Incidence and Mortality in Men

Abstract: Low levels of vitamin D may be associated with increased cancer incidence and mortality in men, particularly for digestive-system cancers. The vitamin D supplementation necessary to achieve a 25(OH)D increment of 25 nmol/L may be at least 1500 IU/day.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

44
766
4
14

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 935 publications
(846 citation statements)
references
References 44 publications
44
766
4
14
Order By: Relevance
“…Epidemiological studies suggest an increased risk of and mortality from cancer in northern latitudes with reduced UVB exposure, an association possibly mediated by vitamin D (107) . Furthermore, prospective cohorts have demonstrated an inverse association between 25(OH)D and cancers of the colon, breast and prostate (108)(109)(110)(111) with one intervention study reporting a reduced risk of cancer by 60 % (112) with levels >80 nmol/l. Ananthakrishnan et al (12) looked at data from 2809 patients with IBD and a median plasma 25(OH)D level of 65 nmol/l.…”
Section: Vitamin D and Cancer In Crohn's Diseasementioning
confidence: 99%
“…Epidemiological studies suggest an increased risk of and mortality from cancer in northern latitudes with reduced UVB exposure, an association possibly mediated by vitamin D (107) . Furthermore, prospective cohorts have demonstrated an inverse association between 25(OH)D and cancers of the colon, breast and prostate (108)(109)(110)(111) with one intervention study reporting a reduced risk of cancer by 60 % (112) with levels >80 nmol/l. Ananthakrishnan et al (12) looked at data from 2809 patients with IBD and a median plasma 25(OH)D level of 65 nmol/l.…”
Section: Vitamin D and Cancer In Crohn's Diseasementioning
confidence: 99%
“…Previous studies on Nurses' Health Study and Health Professionals Follow-up Study have described baseline characteristics of cohort participants and incident colorectal cancer cases, and confirmed that our colorectal cancer cases were well representative as a population-based sample. 28,29 We collected paraffin-embedded tissue blocks from hospitals where cohort participants had undergone resections of primary colorectal cancers. We obtained specimens (hematoxylin and eosin (H&E)-stained slides, unstained slides and/or paraffin blocks) from 648 cases (retrieval rate 76%) in the Health Professionals Follow-up Study and 662 cases (retrieval rate 58%) in the Nurses' Health Study.…”
Section: Study Groupmentioning
confidence: 99%
“…Some 17 studies reported inverse associations between pre-diagnostic vitamin D concentrations and all-18 cancer mortality [12], mortality from colorectal cancer [23,24], prostate cancer [25], and some 19 studies have shown inverse associations between vitamin D concentration at cancer diagnosis and 20 survival [26,27], but not all studies fully support an inverse association [22,23,28]. A cohort analysis 21 that relied on vitamin D status indicators only, estimated that cancer mortality might decrease by 22 29% with an increase in 25(OH)D concentration of 25 nmol/L [29]. Other studies looked at cancer 23 incidence instead of mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Two 10 studies have previously reported moderate [Pearson r = 0.45; [31]] to high [Pearson r = 0.70; [29]] 11 correlations between vitamin D measurements three years apart. In the InCHIANTI study [31], 12 participants with vitamin D levels above and below the median at both blood draws taken three 13 years apart had the lowest and highest rates of mortality, respectively.…”
Section: Introductionmentioning
confidence: 99%